Identification and Characterization of Infectious Pathogens Associated with Mass Mortalities of Pacific Oyster (Crassostrea gigas) Cultured in Northern China - Xiang Zhang; Bo-Wen Huang; Yu-Dong Zheng; Lu-Sheng Xin; Wen-Bo Chen; Tao Yu; Chen Li; Chong-Ming Wang; Chang-Ming Bai (Biology, 2023)
The Pacific oyster (Crassostrea gigas) aquaculture industry increased rapidly in China with the introduction and promotion of triploid oysters in recent years. Mass mortalities affecting different life stages of Pacific oysters emerged periodically in several important production areas of Northern China. During 2020 and 2021, we conducted a passive two-year investigation of infectious pathogens linked to mass mortality. Ostreid herpesvirus-1 (OsHV-1) was detected to be associated with mass mortalities of hatchery larvae, but not juveniles and adults in the open sea. Protozoan parasites, such as Marteilia spp., Perkinsus spp. and Bonamia spp. were not detected. Bacterial isolation and identification revealed that Vibrio natriegens and Vibrio alginolyticus were the most frequently (9 out of 13) identified two dominant bacteria associated with mass mortalities. Pseudoalteromonas spp. was identified as the dominant bacteria in three mortality events that occurred during the cold season. Further bacteriological analysis was conducted on two representative isolates of V. natriegens and V. alginolyticus, designated as CgA1-1 and CgA1-2. Multisequence analysis (MLSA) showed that CgA1-1 and CgA1-2 were closely related to each other and nested within the Harveyi clade. Bacteriological investigation revealed faster growth, and more remarkable haemolytic activity and siderophore production capacity at 25 °C than at 15 °C for both CgA1-1 and CgA1-2. The accumulative mortalities of experimental immersion infections were also higher at 25 °C (90% and 63.33%) than at 15 °C (43.33% and 33.33%) using both CgA1-1 and CgA1-2, respectively. Similar clinical and pathological features were identified in samples collected during both naturally and experimentally occurring mortalities, such as thin visceral mass, discolouration, and connective tissue and digestive tube lesions. The results presented here highlight the potential risk of OsHV-1 to hatchery production of larvae, and the pathogenic role of V. natriegens and V. alginolyticus during mass mortalities of all life stages of Pacific oysters in Northern China.